Poziom i zmiany kapitału własnego a wyniki ekonomiczne gospodarstw indywidualnych - Wasilewski, Mirosław (Level and Changes of the Own Capital Versus Economic Results of the Individual Farms, 2005)
The aim of this study was to analyse relations between economic result of individual farm, and value and changes of own capital. The highest level of the own capital and its increase in the farm, in advantageous way implied profit from the land and social labour productivity. Economic labour productivity in groups of farms excluded with regard to value of own capital was close, however in group of the best increase of capital was the highest. In general, higher value of own capital of the farm was making financial liquidity to grow. Above relation in groups of farms with rise/fall of capital was various.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 447-459